Circulating adiponectin concentration is inversely associated with glucose tolerance and insulin secretion in people with newly diagnosed diabetes. Issue 2 (17th November 2016) - Weber, K. S.; Strassburger, K.; Pacini, G.; Nowotny, B.; Müssig, K.; Szendroedi, J.; Herder, C.; Roden, M.; ,
Abstract: Aims: To examine the hypothesis that changes in serum adiponectin concentration inversely relate to changes in glucose tolerance and β‐cell function already during the early stage of disease progression in recently diagnosed Type 1 and Type 2 diabetes mellitus. Methods: Participants in the prospective observational German Diabetes Study (Type 2 diabetes, n = 94; Type 1 diabetes, n = 42) underwent i.v. glucose tolerance and glucagon stimulation testing to assess pre‐hepatic β‐cell function, glucose tolerance index and C‐peptide secretion within the first year of diabetes diagnosis and 2 years later. Associations of changes in serum concentrations of total adiponectin, high‐molecular‐weight adiponectin and their ratio with changes in the aforementioned metabolic variables were calculated using linear regression. Results: Among people with Type 2 diabetes, 2‐year increases in high‐molecular‐weight adiponectin and in high‐molecular‐weight/total adiponectin ratio were associated with decreases in glucose tolerance index of 0.1%/min ( P = 0.020) and 0.8%/min ( P = 0.013), respectively. Increases in high‐molecular‐weight/total adiponectin ratio were related to decreases in acute C‐peptide secretion of 54.6% ( P = 0.020). Among people with Type 1 diabetes, 2‐year increases in total adiponectin were associated with 2‐year decreases in acute C‐peptide secretion of 56.2% ( P = 0.035). Conclusions: Increases in adiponectin concentrations in the first 2 years after diagnosis were related to a worsening of acute insulin secretion and glucose tolerance index in Type 1 and Type 2 diabetes. (Clinical Trials Registry no.: NCT01055093) What's new?: We show that in people with recently diagnosed Type 1 and Type 2 diabetes, increases in serum concentrations of total and high‐molecular‐weight adiponectin and their ratio were associated with worsening of glucose tolerance index and acute C‐peptide secretion during the early disease course. These findings suggest that, in people with recent diagnosis of diabetes, even those with good glycaemic control, the direction of the association between circulating adiponectin and indicators of cardiometabolic health might be reversed in relation to people with no diabetes.